Associations between physical activity and trimethylamine N-oxide in those at risk of type 2 diabetes. Issue 2 (1st December 2020) - Argyridou, Stavroula; Bernieh, Dennis; Henson, Joseph; Edwardson, Charlotte L; Davies, Melanie J; Khunti, Kamlesh; Suzuki, Toru; Yates, Thomas
Abstract : Introduction: Trimethylamine N -oxide (TMAO) has been identified as a novel gut-derived molecule that is associated with the risk of cardiometabolic diseases. However, the relationship between TMAO and physical activity is not well understood. This study prospectively investigates the association between TMAO and objectively assessed physical activity in a population at high risk of type 2 diabetes mellitus. Research design and methods: Baseline and 12-month follow-up data were used from the Walking Away from Type 2 Diabetes trial, which recruited adults at high risk of type 2 diabetes from primary care in 2009–2010. TMAO was analyzed using targeted mass spectrometry. Generalized estimating equation models with an exchangeable correlation structure were used to investigate the associations between accelerometer-assessed exposures (sedentary time, light physical activity, moderate to vigorous physical activity (MVPA)) and TMAO, adjusting for demographic, clinical and lifestyle factors in varying degrees. Results: Overall, 483 individuals had plasma samples available for the analysis of TMAO (316 (65.4%) men, 167 (34.6%) women), contributing 886 observations to the analysis. MVPA (min/day) was associated with TMAO in all models. In the fully adjusted model, each 30 min or SD difference in MVPA was associated with 0.584 μmol/L (0.070, 1.098) and 0.456 μmol/L (0.054, 0.858) lower TMAO, respectively. Sedentary time and light physical activity were not associated with TMAO in any model. Conclusions: Engagement with MVPA was associated with lower TMAO levels, suggesting a possible new mechanism underlining the inverse relationship between physical activity and cardiometabolic health.